Identifikasi Pepper vein yellows virus yang Berasosiasi dengan Penyakit Yellow Vein Banding pada Tanaman Mentimun di Bali - I Dewa Nyoman Nyana; M. Tinny Lestariningsih; Ni Nengah Putri Adnyani; Gede Suastika (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2016)
Yellowing vein banding disease has been reported infecting cucurbit plants in Bali since 2014. Similar vein banding symptom on chilli pepper was observed previously, and early diagnosis indicated infection of Polerovirus. The objective of this research was to confirm the presence of Polerovirus infection on cucumber plant showing yellow vein banding symptom in Bali. Reverse transcription polymerase chain reaction – based detection method was conducted using specific primer pairs PeVYV-CP-F-BamH1/ PeVYV-CP-R-Pst1followed by sequencing and nucleotide sequence analysis. Specific DNA fragments of ± 650 bp was successfully amplified from field samples. Nucleotide sequence analysis showed that the sequence has the highest similarity > 95% with Pepper vein yellow virus (PeVYV) infecting chili pepper from Indonesia (Bali, and Rembang), Japan, and Greece.